Effect of Temperature Storage on Chemical Properties of Lokio Leaves (Allium chinense G Don) - Dianita Kumalasari; Supriyadi Supriyadi; Andriati Ningrum (Indonesian Food and Nutrition Progress, 2022)
Lokio (Allium chinense G Don) is widely used as seasoning in cooking because it contains amino acids that contribute to taste. Lokio is easily damaged during physical and chemical storage, affecting its quality. The study aims to determine the chemical changes of lokio leaves during storage. This study used a randomized design group with 3 temperature treatments, namely room temperature (30 ⁰C), air conditioning (20 ⁰C), and refrigerator (10 ⁰C). Weight loss was tested using a digital scale, color was tested using a chromameter, water content was tested using thermogravimetry, fat using Soxhlet, protein using Kjeldal, and ash using a muffle furnace. Reducing sugars were tested using the DNS method, amino acids using HPLC, and volatile compounds using GC MS Headspace. The data was analyzed using ANOVA then continued with Duncan test if the treatment has a significant difference (p < 0.05). In the room temperature treatment, the best treatment was obtained for 2 days of storage, AC storage for 4 days, and refrigerator temperature for 14 days of storage. Of all the best treatments for each storage temperature, the best treatment was obtained in the storage treatment using AC temperature (20 ⁰C) for 4 days. The treatment found that Lokio has a water content of 92.247%, fat of 2.47%, protein of 19.05%, ash of 14.20%, carbohydrates of 64.28%, and reducing sugar of 11.24 mg/ml. The major volatile compound content of the total storage is trimethyl sulfide and glutamic acid is the most amino acid in lokio leaves.